2020
DOI: 10.1142/s0217732320400209
|View full text |Cite
|
Sign up to set email alerts
|

Change of sign in the Casimir interaction of peptide films deposited on a dielectric substrate

Abstract: The Casimir free energy and pressure of thin peptide films deposited on a dielectric substrate are investigated in the region of parameters where they change their sign. Numerical computations are performed for a modelled peptide film on a silica glass plate. The Casimir free energy is computed at room temperature as a function of the film thickness and the fraction of water contained in the film. It is shown that the values of the Casimir pressure change from negative to positive when the film thickness decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…As already noted, the stability of molecular films has a critical effect on their applicability for the purposes of biomolecular electronics [ 29 , 70 , 74 , 75 ]. Since the current general trend towards the miniaturization of electronic components has led to the creation of thinner molecular films, the problem of their stability has become more urgent [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already noted, the stability of molecular films has a critical effect on their applicability for the purposes of biomolecular electronics [ 29 , 70 , 74 , 75 ]. Since the current general trend towards the miniaturization of electronic components has led to the creation of thinner molecular films, the problem of their stability has become more urgent [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the current general trend towards the miniaturization of electronic components has led to the creation of thinner molecular films, the problem of their stability has become more urgent [ 76 , 77 ]. In previous work, the authors showed that as film thickness decreases, its stability is influenced by fluctuation forces [ 29 , 70 , 75 ]. The possibility of such an influence was predicted on the basis of previous studies [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-covalent dispersion van der Waals interactions are also thought to play an important role in protein folding [ 16 ] since they make a substantial contribution to protein–protein as well as protein–water interactions [ 17 ]. Additionally, in applications tied to organic optical and electronic devices as well as biotechnology, the contribution of van der Waals interactions to the stability of proteinaceous films deposited on a dielectric substrate has been recently noted [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the dielectric properties of various metals, semiconductors, and insulators, organic as well as inorganic, have been critically assessed in great detail [ 14 ], the dielectric spectrum data for proteins and polypeptides mostly lack the relevant details regarding the optical properties in a wide frequency range from zero frequency to the far ultraviolet [ 18 ]. In the absence of relevant experimental data, the calculated ultraviolet frequency region dielectric spectra for the cyclic tripeptide RGD-4C (1FUV) [ 20 ], based on an ab initio quantum mechanical (QM) computational scheme, were successfully used to calculate the oscillator strengths, oscillator frequencies, and the relaxation parameters that enter the calculations of the van der Waals interactions in proteinaceous systems [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, changes in the control parameter will result in biomolecular thin films of various types and properties. These properties (electrical, optical, mechanical) can be predicted by studying the structures formed as a result of self-organization processes [14][15][16]. Thus, it is necessary to determine the characterization parameters and select methods for studying the resulting dissipative structures.…”
Section: Introductionmentioning
confidence: 99%